IL36 Cooperates With Anti-CTLA-4 mAbs to Facilitate Antitumor Immune Responses - Qu, Qiuxia; Zhai, Zhiwei; Xu, Jieni; Li, Song; Chen, Cheng; Lu, Binfeng (Frontiers in Immunology, 2020)
Despite the great impact on long-term survival of some cancer patients, the immune checkpoint blockade (ICB) therapy is limited by its low response rates for most cancers. There is a pressing need for novel combination immunotherapies that overcome the resistance to current ICB therapies. Cytokines play a pivotal role in tumor immunotherapy by helping initiating and driving antitumor immune responses. Here, we demonstrated that, besides conventional CD4+ and CD8+ T cells, IL36 surprisingly increased the number of tumor-infiltrating regulatory T (Treg) cells in vivo and enhanced proliferation of Tregs in vitro. Administration of CTLA-4 monoclonal antibodies (mAbs) strongly enhanced IL36-stimulated antitumor activities through depletion of Tregs. In addition, a cancer gene therapy using the IL36-loaded nanoparticles in combination with CTLA-4 mAbs synergistically reduced lung metastasis of breast tumor cells. We further showed that the combined therapy of CTLA-4 mAbs and IL36 led to an increase in proliferation and IFN-γ production by CD4+ and CD8+ T cells when compared to single therapy with CTLA-4 mAbs or IL36. Collectively, our findings demonstrated a new combination therapy that could improve the clinical response to ICB immunotherapy for cancer.